REACTIVE OXYGEN SPECIES IN HUMAN SEMEN IN RELATION TO LEUKOCYTE CONTAMINATION - Oborna, Ivana; Fingerova, Helena; Novotny, Jiri; Brezinova, Jana; Svobodova, Magda; Aziz, Nabil (Biomedical papers, 2009)
AIMS: Excessive production of reactive oxygen species (ROS) in semen has been linked to male infertility. Main sources of ROS in male genital tract are immature and/or damaged spermatozoa and a subpopulation of leukocytes known as polymorphonuclear neutrophils (PMN).METHODS: Study group included male partners of infertile couples, 67 normospermic males (group B) and 98 males with sperm abnormalities in one or more parameters (group C), 36 fertile volunteers (group A) served as controls. Sperm parameters were determined according to WHO guidelines. The ROS production was measured by chemiluminiscence in sperm suspension in phosphate buffered saline.RESULTS: All fertile volunteers in the control group had seminal PMN concentrations below 0.5x106/ml. Therefore study subjects, 67 normospermic and 98 men with sperm abnormalities, were further subdivided into two subgroups of PMN concentrations: (1) < 0.5x106/ml and (2) 0.5 to 1.0x106/ml. The ROS production in individuals varied greatly from 1.0x102 to 1.7 x107 RLU/min per 20x106 spermatozoa. The ROS production in both subgroups of normospermic men and the subgroup (1) of men with sperm abnormalities was not different from the ROS production in fertile controls. The ROS production in the subgroup (2) with sperm abnormalities was significantly higher than in controls (P = 0.00004).CONCLUSIONS: Our findings suggest that the contribution of PMN to the ROS production in semen is negligible only up to a concentration of 0.5x106/ml. This suggests that the current WHO Guidelines threshold of 1.0x106 PMN per ml of semen is too high and might be re-evaluated.
Keywords: Reactive oxygen species/Polymorphonuclear neutrophils/Human spermatozoa/Male infertility